Nursing teamwork in the care of older people: A mixed methods study. (October 2019) - Anderson, J.E.; Ross, A.J.; Lim, R.; Kodate, N.; Thompson, K.; Jensen, H.; Cooney, K.
Abstract: Healthcare is increasingly complex and requires the ability to adapt to changing demands. Teamwork is essential to delivering high quality care and is central to nursing. The aims of this study were to identify the processes that underpin nursing teamwork and how these affect the care of older people, identify the relationship between perceived teamwork and perceived quality of care, and explore in depth the experience of working in nursing teams. The study was carried out in three older people's wards in a London teaching hospital. Nurses and healthcare assistants completed questionnaires (n = 65) on known dynamics of teamwork (using the Nursing Teamwork Survey) together with ratings of organisational quality (using an adapted AHRQ HSPS scale). A sample (n = 22; 34%) was then interviewed about their perceptions of care, teamwork and how good outcomes are delivered in everyday work. Results showed that many care difficulties were routinely encountered, and confirmed the importance of teamwork (e.g. shared mental models of tasks and team roles and responsibilities, supported by leadership) in adapting to challenges. Perceived quality of teamwork was positively related to perceived quality of care. Work system variability and the external environment influenced teamwork, and confirmed the importance of team adaptive capacity. The CARE model shows the centrality of teamwork in adapting to variable demand and capacity to deliver care processes, and the influence of broader system factors on teamworking. Highlights: Perceived quality of care was related to perceived quality of teamwork and leadership. Challenges included the difficult nature of caring for older people and time pressures. Nurses co-ordinated a multi-disciplinary team. Adapting to constantly changing priorities was made difficult by role confusion and unclear expectations.